Distributed Fiberoptic Sensor for Simultaneous Temperature and Strain Monitoring Based on Brillouin Scattering Effect in Polyimide-Coated Fibers - Sheng, Liwen; Li, Ligong; Hu, Leijun; Yuan, Ming; Lang, Jinpeng; Wang, Jianguo; Li, Peng; Bi, Zongyi; Yan, Jisong; Liu, Zhiming (International Journal of Optics, 2020)
A unique multiparameter sensor for distributed measurement of temperature and strain based on spontaneous Brillouin scattering in polyimide-coated optical fiber is proposed, which is an excellent candidate for the cross-sensitivity problem in conventional Brillouin sensing network. In the experimental section, the discrimination of strain and temperature is successfully demonstrated by analysing the unequal sensing coefficients of the Brillouin frequency shifts generated by different acoustic modes. The Brillouin frequency shifts of the main two peaks are successfully measured to discriminate the strain and temperature with an accuracy 19.68 με and 1.02°C in 2.5 km sensing range. The proposed distributed Brillouin optical fiber sensor allows simultaneous measurement of temperature and strain, thus opening a door for practical application such as oil explorations.